If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(3) = (2x + -8) Reorder the terms for easier multiplication: 3f = (2x + -8) Reorder the terms: 3f = (-8 + 2x) Remove parenthesis around (-8 + 2x) 3f = -8 + 2x Solving 3f = -8 + 2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '3'. f = -2.666666667 + 0.6666666667x Simplifying f = -2.666666667 + 0.6666666667x
| 7m(m-1)=4(m-1) | | 4r(p-7q)+3(p-7q)= | | (1/2)(116-x)=20 | | f(2)=3x-1 | | -5(v+3)+2v+5=8v+8 | | 7x^2+7y^2-28x+42y-35=0 | | 9.1/(x-5.7)=1.4 | | X-9=-5-9 | | 5mn+5mp-2n-2p= | | (5/8x)-(1/2)=(1/5) | | 70=w^3-4 | | x+4=g | | f(0)=(2x-8) | | -38+9+y=-12+16 | | 5(x-6)-6x(x-5)=x+5-(x-4) | | 1900+5x=2 | | 17x-5=14x-8 | | 7/22x11/35 | | y=2x+5cos^3x | | -3(x+4)=2(x-5) | | 0=x^4-3x^3-8x^2+12x+16 | | 3x-2=-2x-8 | | 30x=6x | | -5(4x+1)-5=-3(x+4)+2x | | 15-6n+2=4n-1 | | y=xsquared+1 | | 11x+13=55 | | -10z=2.7 | | 4-3m=-4m+5 | | 15x=11000 | | 10-6=4 | | 10z=2.7 |